Analisis Hasil Belajar Ditinjau dari Minat Belajar Matematika Kelas VII SMP Negeri 5 Tanggetada - Gemi Susanti; Jahring; Marlina (Arus Jurnal Pendidikan, 2021)
The background to this research is that the learning outcomes of students at SMPN 5 Tanggetada are still relatively low, which is closely related to interest in learning. This study aims to describe the learning outcomes in terms of interest in learning mathematics at SMP Negeri 5 Tanggetada. This research was conducted in the odd semester of the 2020/2021 academic year at SMPN 5 Tanggetada. This type of research is qualitative descriptive. The subjects of this study consisted of 27 grade 7 students from SMP Negeri 5 Tanggetada. The research instruments used were: (1) a mathematics learning outcomes test consisting of 5 items; (2) interviews; (3) a learning interest questionnaire consisting of 13 statements. The results obtained: 1) there is 1 student who has high learning outcomes with high interest in learning, there is 1 student who has moderate learning outcomes with high interest in learning, 1 student with low learning outcomes with a moderate interest in learning; 2) For high grade learning outcomes there are 11 students, for medium learning outcomes there are 7 students and low grade there are 9 students. 3) For the high interest category for learning there are 2 students, for the medium category there are 17 students and for the low category there are 8 students.